Determinantes da intenção de compra em supermercados online em Portugal - d´Aguiar, Mariana Leal Palma Fernandes (2021)
Dissertation presented as the partial requirement for obtaining a Master's degree in Statistics and Information Management, specialization in Information Analysis and Management